2011
DOI: 10.1007/s11192-011-0523-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between co-authorship, currency of references and author self-citations

Abstract: This paper attempts to identify the relationship between co-authorship and the currency of the references and author self-citations in the key journals of environmental engineering. The results show that the self-citation rate of co-authored articles is higher than in single-authored articles. A statistically significant correlation is identified between the numbers of co-authors, the rate of author self-citing and the author self-cited; though it was a low correlation. The value of coefficient correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
(44 reference statements)
2
12
0
Order By: Relevance
“…Statistically significant correlation was observed between total reference count and year of publication (r=.246; p<.01; n=1503). The current finding is in conformity with the results of Lin and Huang (2012) who also observed that with the passage of time authors tend to cite more. Regarding quantity of self-citations, there also exists relation between these two variables (r=.108; p<.01; n=1503).…”
Section: Publication and Reference Behaviour Of Authors Over Timesupporting
confidence: 93%
See 1 more Smart Citation
“…Statistically significant correlation was observed between total reference count and year of publication (r=.246; p<.01; n=1503). The current finding is in conformity with the results of Lin and Huang (2012) who also observed that with the passage of time authors tend to cite more. Regarding quantity of self-citations, there also exists relation between these two variables (r=.108; p<.01; n=1503).…”
Section: Publication and Reference Behaviour Of Authors Over Timesupporting
confidence: 93%
“…Thus, it is clear that self-citations are much younger than other citations. Regardless of whether the study is conducted through synchronous or diachronous approach, authors have also observed that self-citations tend to be more for recent works than citations to other works (Lin and Huang 2012;Synder and Bonzi 1998;Tagliacozzo 1977). Amongst the most probable reasons, such behaviour may be attributed to limited research experience of authors.…”
Section: Currency Of Self and Other Referencesmentioning
confidence: 99%
“…These files were postprocessed in order to extract the number of references and the number of pages per paper since 1972. As previously reported [8], these automatically generated data sets may contain a significant number of errors, particularly in the older files that have been generated with OCR systems fed with the paper editions of the journals. In order to check possible mistakes, a random set of papers with a too low number of references (0, 1 and 2) were inspected by hand.…”
Section: Methodsmentioning
confidence: 99%
“…Lin and Huang [8] analyze the number of references in environmental engineering articles by year, in a 10-year interval (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) and demonstrate a slightly increasing tendency, with an average number of 33.08 references.…”
Section: Introductionmentioning
confidence: 99%
“…Second, due to authors' self-citations (Lin and Huang 2012), the average number of authors per international co-authored article was included as another control variable (Biscaro and Giupponi 2014). Because previous studies found that citation counts increased over time (Kellsey and Knievel 2004), the third control variable was the publication year of the articles.…”
Section: Control Variablesmentioning
confidence: 99%